2017
DOI: 10.1080/17475759.2017.1386122
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation Preferences, Ethnic and Religious Identification and the Socio-Economic Adaptation of Russian-Speaking Immigrants in Belgium

Abstract: His interest center on cross-cultural psychology including the role of ecological and cultural factors in development, and the psychology of acculturation and ethnic relations in plural societies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 76 publications
6
18
1
Order By: Relevance
“…Narratives in the current study suggest that the structural and socio-economic conditions in Albania, for example, were not viewed as facilitating utilisation of the skills returnees had acquired during their migration and limited the extent to which they could invest in business opportunities. This is consistent with other researches indicating that local economic contexts do not always facilitate the conversion of capital and that immigrants can find it difficult to secure upward mobility vis-à-vis locals (Grigoryev and Berry 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Narratives in the current study suggest that the structural and socio-economic conditions in Albania, for example, were not viewed as facilitating utilisation of the skills returnees had acquired during their migration and limited the extent to which they could invest in business opportunities. This is consistent with other researches indicating that local economic contexts do not always facilitate the conversion of capital and that immigrants can find it difficult to secure upward mobility vis-à-vis locals (Grigoryev and Berry 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Previous literature has generally shown that the integration strategy appeared to be both the most preferential and successful, and it had a positive relationship with people's psychological adjustment (e.g. Berry, 1997Berry, , 2005Grigoryev and Berry, 2017;Gui et al, 2016;Nguyen and Benet-Martinez, 2013). It was interesting that our study found that the positive separation strategy was preferred by the Chinese expatriates, and this was conducive to their psychological adjustment.…”
Section: Notessupporting
confidence: 47%
“…Likewise, when separation and marginalization are imposed by the dominant group instead adapted by ethnocultural groups, it takes the form of other strategies known as segregation and exclusion, respectively. Finally, when cultural diversity is respected by larger society allowing the inclusion of the other ethnocultural groups, the phenomenon is called multiculturalism (Berry, 2011;Grigoryev & Berry, 2017). This encourages a pluralistic model that serves to pursue shared national goals and needs by dealing with distinct cultures and allowing diverse cultural groups to work with each other (LaFromboise et.…”
Section: Intercultural Strategies and Integrationmentioning
confidence: 99%
“…al., 1993). However, inconsistencies and conflicts between the preferences of non-dominant groups for the acculturating strategies they employ and the forced alternative strategies enacted by the larger society cause difficulties for the acculturating groups or individuals, which is called acculturative stress (Berry, 2011;Grigoryev & Berry, 2017). Several studies show that individuals were engaged in these four intercultural strategies.…”
Section: Intercultural Strategies and Integrationmentioning
confidence: 99%